Earth materials - Hefferan, Kevin; O'Brien, John (Hoboken, NJ : Wiley, 2022)
'Earth Materials encompass the minerals, rocks, soil and water that constitute our planet and the physical, chemical and biological processes that produce them. Since the expansion of computer technology in the last two decades of the 20th century, many universities have compressed or eliminated individual course offerings such as mineralogy, optical mineralogy, igneous petrology, sedimentology and metamorphic petrology and replaced them with Earth materials courses. Earth materials courses have become an essential curricular component in the fields of geology, geoscience, Earth science, engineering geology, environmental geology and many related areas of study. This textbook is designed to address the needs of a one or two semester Earth materials course, as well as individuals who want or need an expanded background in minerals, rocks, soils and water resources'--
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Geology -- Textbooks; Earth sciences -- Textbooks